Business Process Reengineering pada Sistem Pemesanan Travel di Intan Travel - Hidayatullah, Nailul Faiz; Nuryasin, Ilyas (Computer Science and Information Technology, 2024)
In the era of technological development, travel service companies like Intan Travel in Tabalong Regency, South Kalimantan, face challenges in improving service quality and operational efficiency. Intan Travel currently relies on WhatsApp for ticket booking and cash payments after the trip, which reveals weaknesses in business process effectiveness and efficiency. This study applies Business Process Reengineering (BPR) which involves a thorough analysis of existing business processes, identification of unnecessary activities, and redesigning the workflow to optimize efficiency and reduce errors. This study uses the mapping standards of the American Society of Mechanical Engineers (ASME) to measure efficiency and throughput speed. The technical processes carried out include data collection, process mapping, performance measurement, identification of bottlenecks, and the application of information technology for system automation and integration. The results of this study show that after the implementation of BPR, the efficiency of the room rental process increased from 47.36% to 92.28%. The implementation of BPR in Intan Travel's booking system opens up opportunities for comprehensive and optimal business process revolution, enabling more competitive market performance.